Extensively-Drug Resistant Klebsiella pneumoniae Recovered From Neonatal Sepsis Cases From a Major NICU in Egypt - Hassuna, Noha A.; AbdelAziz, Reem A.; Zakaria, Amira; Abdelhakeem, Mohammed (Frontiers in Microbiology, 2020)
Background: Neonatal sepsis is a great defiance to clinicians and medical microbiologists, particularly those cases caused by Klebsiella pneumoniae. Thus, we aimed at investigating the profile and mechanisms of antibiotic resistance and the clonal relationships between K. pneumoniae isolated from neonates at the largest tertiary care hospital’s neonatal intensive care units (NICUs) in Minia, Egypt. Methods: This study comprised 156 neonates diagnosed with culture-proven sepsis from February 2019 to September 2019, at a major neonatal intensive care unit (NICU) of Minia City. All K. pneumoniae isolates were collected and characterized: antimicrobial profile, resistance genotype and PFGE typing. Results: Twenty-four K. pneumoniae (15.3%) were collected, showing extensive drug resistance (XDR) to most of the antimicrobials except fluroquinolones. All the isolates possessed blaVIM and blaNDM carbapenemase genes, while blaKPC gene was detected in 95.8% of the isolates. Considering ESBL genes, blaCTX-M was found in all the isolates and blaOXA-1 gene in 75% of them. The PMQR gene qnrS was predominantly found among our isolates compared to qnrB or qnrA. Moderate degree of clonal relatedness was observed between the isolates. Conclusion: To the best of our knowledge, this the first report of an alarming occurrence of XDR among K. penumoniae isolates recovered from neonatal sepsis in Egypt. Our data necessitates proper antimicrobial stewardship as the choices will be very limited.